A2A R mediated modulation in IP3 levels altering the [Ca2+]i through cAMP-dependent PKA signalling pathway - Barodia, Sandeep Kumar; Sophronea, Tuithung; Luthra, Pratibha Mehta (Biochimica et biophysica acta. General subjects, 2022)
Stimulation of A2A receptors (A2A R) coupled to Gs/olf protein activates Adenylyl cyclase (AC) leading to the release of cAMP which activates the cAMP-dependent PKA phosphorylation. The possible role of A2A R in the modulation of free cytosolic Ca2+ concentration ([Ca2+]i) involving IP3, cAMP and PKA was investigated in HEK 293-A2A R. The levels of IP3 and cAMP were observed by enzyme immunoassay detection method and [Ca2+]i using Fluo-4 AM. Moreover, cAMP-dependent PKA was determined using the PKA Colorimetric Activity Kit. We observed that the cells pre-treated with A2A R agonist NECA showed increased levels of cAMP, PKA, IP3 and [Ca2+]i levels. However, the reverse effect was observed with A2A R antagonists (ZM241385 and caffeine). Blocking the Gαq/PLC/DAG/IP3 pathway with neomycin, a PLC inhibitor did not affect the modulation of IP3 and [Ca2+]i levels in HEK 293-A2A R cells. To investigate the Gαi/AC/cAMP/PKA, HEK 293-A2A R cells pre-treated with pertussis toxin followed by forskolin in the presence of A2A R agonist (NECA) showed no effect on cAMP levels. Further, Gαs/AC/cAMP/PKA pathway was investigated to elucidate the role of cAMP-dependent PKA in IP3 mediated [Ca2+]i modulation. In the HEK 293-A2A R cells pre-treated with PKA inhibitor KT5720 and treated with NECA led to inhibit the IP3 and [Ca2+]i levels. The study distinctly demonstrated that A2A R modulates IP3 levels to release the [Ca2+]i via cAMP-dependent PKA. The role of A2A R mediated Gαs pathway inducing IP3 mediated [Ca2+]i release may open new avenues in the therapy of neurodegenerative disorder. •[Ca2+]i signalling pathways via A2A R in HEK 293-A2A R cells have been studied.•A2A R mediated [Ca2+]i signalling pathways viz. Gαq/PLC/DAG/IP3, Gαi/AC/cAMP/PKA and Gαs/AC/cAMP/PKA have been investigated.•We first time demonstrated that A2A R mediated Gαs /AC/cAMP/PKA signalling pathway modulated the cAMP/PKA levels releasing the IP3 and [Ca2+]i.